(untitled) - King, Julie Adair (Hoboken, N.J., 2013)
The Nikon D600 is a professional-level full-frame sensor that is sure to attract an audience of DSLR newcomers and pros. This friendly-and-thorough full-color guide shows you how to get a firm grasp on this powerful camera and helps you to ultimately get better photos.
Keywords: Canon digital cameras,Photography,Máy ảnh kỹ thuật số Nikon,Nhiếp ảnh; Digital techniques,Kỹ thuật số